Influence of the Stimulant Humimax on the Yield of Sunflower (Texas Journal of Agriculture and Biological Sciences, 2022)
In the conditions of the Surkhandarya region, the use of growth stimulants Humimax to obtain an early and high-yielding re-crop of sunflower. With the use of growth stimulants Humimax (seeding rate 0.75 l/t; spraying of plants in phase 3-4 leaves 0.4 l/ha) had a positive effect on all seed, growth, development and productive seed